The Subject in the City: psychoanalysis, social bond and invention - Sébastien Ponnou (Universidade Federal do Rio Grande do Sul, 2021)
The clinic testifies daily the symbolic and imaginary treasures that adolescents draw on the city in order to face the complex psychic and social situations. If we consider the social bond as a fact of language, or a particular way of inscribing the subject in language, then psychoanalysis becomes an inexhaustible resource in the accompaniment and support of these vulnerable adolescents. We will discuss this proposal with reference to the teachings of Sigmund Freud, Jacques Lacan, and Jacques-Alain Miller - and with the support of a clinical presentation taken from our practice with adolescents.